A study on implementation of national programme for prevention and control of cancer, diabetes, cardiovascular diseases and stroke in Udupi district, Karnataka - Ainapure, Kantinath; Sumit, Kumar; Pattanshetty, Sanjay M. (International Journal Of Community Medicine And Public Health, 2018)
Background: In India National programme for prevention and control of Cancer, Diabetes, Cardiovascular Diseases and Stroke (NPCDCS) programme was launched in 2011 to reduce the burden of Non-Communicable diseases (NCDs). Udupi district was one of the first few districts of Karnataka where NPCDCS programme was started in the year 2010. Methods: A qualitative cross-sectional study was conducted among the stakeholders involved in the NPCDCS programme of Udupi District, Karnataka from January 2017- June 2017. Purposive sampling method was used for the sample selection. A total of 36 in-depth interviews were carried out among the stakeholders of NPCDCS programme. Results: The programme has achieved initial success and its successful implementation has to be observed in the coming years. Health staff posts which are critical in implementation of NPCDCS are vacant in many of the healthcare centres. Awareness about this programme was relatively low in the community. Conclusions: It is necessary to conduct regular awareness and screening campaigns with proper follow-up services to make the community sensitized about the programme. Regular supply of medicines should be ensured for the effective implementation of the programme in the future so that it can achieve its goal in reducing the burden NCDs.